2004
DOI: 10.1002/jrs.1209
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Raman spectroscopy of ancient ceramics: a study of French sigillata wares

Abstract: Micro-Raman spectroscopy was applied to the study of some French sigillata wares dating back to the end of the 1st century AD and coming from two important Roman ceramic production centres at La Graufesenque (Aveyron) and Glanum in Saint Rémi de Provence. The differentiation between the mineralogical composition of the reddish bright slip and the porous ceramic body underneath was accomplished, confirming the previous hypothesis by the CNRS research group at Toulouse that a different and finer clay material wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
45
1
1

Year Published

2004
2004
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 4 publications
3
45
1
1
Order By: Relevance
“…1 -4 Among the main results concerning the fabrication process, it has been shown that different clays were used for the body and slip preparations. 1,3 The main ceramic piece was made with calcareous clay, whereas a very fine and purified noncalcareous clay was in turn applied, giving rise to the typical red and waxy shining varnish. The firing temperature 2 was typically between 1020 and 1080°C.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 -4 Among the main results concerning the fabrication process, it has been shown that different clays were used for the body and slip preparations. 1,3 The main ceramic piece was made with calcareous clay, whereas a very fine and purified noncalcareous clay was in turn applied, giving rise to the typical red and waxy shining varnish. The firing temperature 2 was typically between 1020 and 1080°C.…”
Section: Introductionmentioning
confidence: 99%
“…8 Moreover, its use as a non-destructive and non-invasive microprobe investigation method for ceramic materials has been profusely discussed. 3,4,9,10 This peculiarity would also meet all the conditions for a micro-scale investigation of hematite within the slip layer: a study aimed to identify spectral markers imputable to structural modifications and thus to a firing and/or compositional effect. Another advantage is represented by the lack of sample preparation and the fast response, so that a statistical survey could be conducted in a reasonably short time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this communication, we present some results obtained by the use of two complementary laser techniques: micro-LIBS and micro-Raman spectroscopy; in particular, the micro-Raman analysis can give mainly qualitative information about the material's molecular structure, whilst the LIBS technique permits also quantitative albeit elemental measurements [3][4][5][6]. Moreover, the Raman microscopy is very selective, even if the Raman signal is not too high and in competition with the fluorescence phenomenon, particularly in the case of pigments or organic binding media [7,8]. In recent years, several groups have proposed the use of laser induced breakdown spectroscopy (LIBS) as a technique capable of giving information on the pigment compositions with minimal damage of the artwork [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…El examen científico de estas cerámicas puede aportar información valiosa a la investigación arqueológica tanto en la asignación de procedencias como en el redescubrimiento de las tecnologías de producción [2,3]. Con este propósito se han venido utilizando distintas técnicas de microscopía (óptica y electrónica) y espectroscopías de tipo electrónico, atómico, molecular, nuclear o de rayos-X; pudiendo establecerse una clasificación de las mismas en dos grandes grupos: aquellas técnicas que pueden aportar información cualitativa o cuantitativa de microdominios homogéneos en cada pieza [4][5][6][7][8][9][10][11][12][13][14] y las utilizadas para el análisis cuantitativo de series de muestras, como método para establecer agrupamientos e identificar procedencias [9,10,[15][16][17][18][19][20]. En general, todas ellas requieren la preparación de muestras (fragmentación, pulverización, o disolución) y sólo pueden llevarse a cabo como métodos de laboratorio.…”
Section: Introductionunclassified